PENGARUH PROFESIONALISME, ETIKA, PENGALAMAN, PENGETAHUAN DAN KUALITAS AUDIT TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS AKUNTAN PUBLIK - MUGIA LESTARI, ANINDY (Jurnal Akuntansi AKUNESA, 2015)
This research is a quantitative study aimed to obtain empirical evidence about the influence of professionalism, professional ethis, experience auditor, knowledge in detecting fraud and errors and quality audit on consideration of materiality level of public accounting (materiality judgment). The method of determination sample used was purposive sampling. The data used were primary data collected through questionnaires. The questionnaires distributed numbered 130 copy but only 110 copy question returned. Meanwhile, to answer the research hypotheses data analysis method used is to thes the quality of data which include validity, reliability, hypothesis testing.the statistical method using a multiple regression analysis. Based on these results it can be concluded that the variable Professionalism, professional ethis, experience auditor, Knowledge Detect fraud and error, and quality audit and jointly significant influence Materiality Level Advisory Public Accountants. Keywords: professionalism, ethis, experience, Knowlegde, quality audit, materiality